1998
DOI: 10.1007/s004310050928
|View full text |Cite
|
Sign up to set email alerts
|

Disease-related response to inhaled nitric oxide in newborns with severe hypoxaemic respiratory failure

Abstract: Inhaled nitric oxide (iNO) has been shown to improve oxygenation in severe persistent pulmonary hypertension of the newborn (PPHN). However, PPHN is often associated with various lung diseases. Thus, response to iNO may depend upon the aetiology of neonatal acute respiratory failure. A total of 150 (29 preterm and 121 term) newborns with PPHN were prospectively enrolled on the basis of oxygenation index (OI) higher than 30 and 40, respectively. NO dosage was stepwise increased (10-80 ppm) during conventional m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
35
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 32 publications
0
35
1
1
Order By: Relevance
“…iNO is the first-line pulmonary vasodilator in many centers for the treatment of neonatal hypoxemic respiratory failure, but the response can be variable. For example, in meconium aspiration syndrome, it has been suggested that the effective alveolar distribution of iNO may be limited by meconium in the airways and that this may in part account for the variable response that has been described in this group (13). Nitric oxide alone is not always sufficient to break the vicious cycle of hypoxemia and pulmonary hypertension; thus, a percentage of infants continue to require extracorporeal life support, and a minority still die.…”
Section: Discussionmentioning
confidence: 99%
“…iNO is the first-line pulmonary vasodilator in many centers for the treatment of neonatal hypoxemic respiratory failure, but the response can be variable. For example, in meconium aspiration syndrome, it has been suggested that the effective alveolar distribution of iNO may be limited by meconium in the airways and that this may in part account for the variable response that has been described in this group (13). Nitric oxide alone is not always sufficient to break the vicious cycle of hypoxemia and pulmonary hypertension; thus, a percentage of infants continue to require extracorporeal life support, and a minority still die.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 In both primary and secondary persistent pulmonary hypertension of the newborn, INO improves oxygenation, reduces the need for ECMO, or improves neurodevelopmental outcomes when other therapies fail. [10][11][12][13] Clinicians have hoped that pulmonary hypertension in patients with CDH would respond similarly; however, no randomized trial has demonstrated that INO improves outcomes in these patients. Two well-designed, methodologically sound trials found that early INO treatment fails to improve survival or reduce need for ECMO in newborns with CDH.…”
mentioning
confidence: 99%
“…In recent years, treatments for PPHN have been aimed at controlling or reversing the pulmonary endothelial dysfunction, which otherwise rapidly initiates the unrelenting cascade of pulmonary hypertension, right-toleft shunting, and hypoxemia. iNO has an important role in the acute management of pulmonary hypertension (14). However, the limited response in some patient groups, the potential for rebound upon iNO withdrawal, and more recent financial implications of long-term iNO therapy, coupled with our increasing understanding of other important molecular pathways in the pathophysiology of pulmonary hypertension, remain compelling stimuli for research into other agents (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…iNO improves oxygenation and reduces the need for extracorporeal life support in some of the most severe cases (13). However, the individual response to iNO is disease specific (13,14). In infants with meconium aspiration syndrome, the distribution of iNO, and its subsequent efficacy, can be limited by the presence of meconium in the airways, reduced surfactant activity, and widespread ventilation-perfusion mismatch (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation